Men and anti-violence initiatives: transnational feminist reflections from Afghanistan and Pakistan. Issue 10 (3rd October 2019) - Wu, Joyce
Abstract: This article looks at how international development's rhetoric for enlisting men to take up anti-violence against women's work is translated into reality. Based on fieldwork conducted in Afghanistan and Pakistan, I argue that whilst there have been success stories of men's behaviour changing, the localisation of gender concepts and ideas into local frameworks has not been as successful. Furthermore, inattention to how gender relations are shaped by conflict and violence results in the dilution of feminist values around work on violence against women. This inattention also privileges middle-class men's activism at the expense of activism by women and men from lower-socioeconomic backgrounds. The article concludes with a call for further transnational feminist dialogue and interventions in the area of men's involvement, so that current and future initiatives are critical, reflexive and relevant.